(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article provides information on the development of ecological education in Oktog state reserve. By the decision of the President of the Republic of Uzbekistan No. 131 dated February 16, 2022, the Oktog-Tomdi state reserve was established on the territory of Shiyeli OFY, Tomdi District, Navoi Region, on an area of 40,000 hectares.